Context Mobile Application (CMA) for Increasing the Service of Koperasi in Indonesia - Rijois Iboy Erwin Saragih; Rahmadani Rahmadani (Institut Bakti Nusantara, 2022)
Koperasi has an important role for economic growing in Indonesia. Especially in this time of pandemic, all countries in this world are face the same problem because of Covid-19 which is economic collapse beside the health issues. It is already a year that this virus affects the economic system of the countries. The government tries to grow the economic by supporting the small businesses through keperasi perhaps they may help the growing of the economics of the country. Unfortunately, most of conventional koperasi are still use the manual system to operate their serving to the member. In this research, it proposes mobile application of koperasi based on context needed in order to give better services to the member. The result of this research shows more than 80% user satisfy using this application.